Maternal and foetal outcomes in referred obstetric cases at a tertiary care centre in Lumbini Province, Nepal - Subedi, Jigyasa; KC, Tara; Sharma, Deepanjali; Lamsal, Manoj; Banu, Hasina; Thakur, Sabnam; Chaube, Vivek; Laxmi Manandhar, Bekha (Journal of Chitwan Medical College, 2025)
Introduction: An effective referral system is essential for ensuring continuity of obstetric care to prevent maternal morbidity and mortality. This study was conducted with an objective to find out reasons for obstetric referrals, maternal and perinatal outcome in a tertiary care centre of Nepal. Method: This descriptive, cross-sectional study was conducted at Universal College of Medical Sciences Nepal, from 01 Oct 2021 to 31 Mar 2022. The study analysed obstetric referral cases, focusing on referral indications, clinical examinations, investigations, and interventions performed. Referred antenatal and intrapartum cases of gestational age ≥28 weeks who delivered at study centre was included. Postpartum cases, gestation <28 weeks, undocumented referrals, follow-up cases booked at study centre, and gynaecological referrals were excluded. Data were analysed descriptively for frequencies, percentages, and means using SPSS-20. Result: Out of 403 referred cases that met inclusion criteria (25.6% out of a total of 1573 deliveries), 191(47.3%) were in the age group of 20-24 years. The main reasons for referral were for better facilities (safe delivery) 115(28.6%), preterm labour 105(26.1%), preeclampsia 34(8.5%), and malpresentation 20(5%). Lower segment caesarean section was the common mode of delivery 202(50.1%). Postpartum haemorrhage 37(9.2%) was a common complication. Total of 79(19.6%) neonates required NICU admission. There were 3(0.7%) maternal deaths. Conclusion: Better facilities, preterm labour, preeclampsia, and malpresentations were causes of obstetrics referrals. High caesarean rate and NICU admission rates reflect case severity. However, maternal deaths and stillbirths persisted despite of advanced care.